Production Cost Analysis of Broiler Business with Semi Closed House System - Cori Qamara; Widiarta, I Putu Gede Didik; Aldiyanti, Amani; Fatmarischa, Novemia; Wijakesuma, Made Herdinata (Journal of Agriprecision & Social Impact, 2025)
This study aims to analyze the production costs of the boriler chicken farming business with a semi-closed house system with a population of 1000 chickens. The case study approach is the methodology employed in this study. Two categories of data are utilized: primary and secondary. Recording pricing from owners is the primary source of data. Reading resources that are secondary data and are taken from government records and earlier studies. The following cost formulas were used to examine the data: depreciation costs, variable costs, total costs, total revenue, profit, R/C, and BEP. The components of cages are sufficiently advanced to reduce the negative environmental effects on broilers. Semi-closed house cages are more affordable than closed house cages, despite having technology-based component. The result shows that that feed expenses are the most expensive aspect of manufacturing. The total cost for one semi-closed house cage with a population of 1000 chickens is IDR 49,469,122. The total revenue in this study was IDR 51,045,000 and profit was IDR 1,575,878/periode. The value of R/C for semi-closed house system in this study was 1.03. A semi-closed house farm with 1000 broilers has a BEP price of IDR 49,469.12/Kg.  It is possible to operate a broiler farm with 1000 chickens using a semi-closed system. In light of the semi-closed house system broiler business's production expenses, it is hoped that the study's findings will serve as a reference for readers.